2012
DOI: 10.1002/ejlt.201100147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TAG composition on performance of low saturate shortenings in puff pastry

Abstract: Four blends formulated with low saturated fatty acid content, with the saturated component rich in stearic acid, were prepared from shea stearin, interesterified shea stearin, fully hardened soybean oil and high oleic sunflower oil in order to study their performance as shortenings in puff pastry products. The blends had a low saturated fatty acid content (30.1 AE 1.1%) compared to butter (65.9%). Saturates in the four blends examined came mainly from SSS, SOS, SSO and SOO. Puff pastry prepared from the blend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Given the notoriously high solid fat content (SFC) of laminating shortening products, the SFC of CLS was compared to Coasun Classic (Garcia-Macias et al, 2012;Patient, 2006). At 20°C, the SFC of Coasun Classic is 6.48 ± 0.49%, and the SFC of CLS is 35.65 ± 0.83%, almost 6 times greater.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the notoriously high solid fat content (SFC) of laminating shortening products, the SFC of CLS was compared to Coasun Classic (Garcia-Macias et al, 2012;Patient, 2006). At 20°C, the SFC of Coasun Classic is 6.48 ± 0.49%, and the SFC of CLS is 35.65 ± 0.83%, almost 6 times greater.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, these criteria are met by incorporating solid fat with high melting triacylglycerol (TAG) components into the shortening composition (Garcia-Macias, Gordon, Frazier, Smith, & Gambelli, 2012). This obviously reduces the nutritional quality of the food product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with the findings of Garcia-Macias et al (2011, who reported a lower lift for puff pastry produced with vegetable roll-in fats compared to puff pastry containing butter (66 % SAFA). These studies used FBs which contained about 30 % SAFA, namely palmitic acid (Garcia-Macias et al 2011) and stearic acid, respectively (Garcia-Macias et al 2012).…”
Section: Puff Pastry Qualitymentioning
confidence: 99%
“…Several studies addressing the reduction of fat, SAFA and TFA in puff pastry have been performed (Boode-Boissevain and Van HoudtMoree 1996; Simovic et al 2009;Garcia-Macias et al 2012). The majority of studies focussed on the characteristics of shortenings and fats used in puff pastry production, e.g.…”
Section: Introductionmentioning
confidence: 99%